Systematic review of aquatic physical exercise programs on functional fitness in older adults - Jose Fuentes-Lopez; Ruben Vidal-Espinoza; Fernando Alvear-Vasquez; Lucila Sanchez-Macedo; Dony Mamani Velasquez; Wily Rivera Pacco; Marco Cossio-Bolaños; Rossana Gomez Campos (PAGEPress Publications, 2021)
The practice of physical exercise is recommended in the prevention of the deterioration of neuromuscular functions in aging. The objectives of this systematic review were to describe the protocols used and the functional fitness indicators evaluated in aquatic exercise programs in adults aged 50 to 80 years. The Pubmed database was used. The keywords were: 1) Physical exercise program or protocols or duration or type of exercise or aquatic exercise, frequency or intensity or indicators; 2) Adults or older adults; 3) Training or indicators, functional fitness, physical fitness. The search strategy considered the components of the Population, Interventions, Comparators, Outcomes, and Study design (PICOS) tool. Nine experimental studies were identified. These studies developed protocols to improve functional fitness in adults aged 50 to 80 years. They were based on sessions of 2 to 5 per week, the work time per session was 30 to 60min, intensities varied between 50 to 95% and totaled between 4 to 24 weeks of intervention. The activities were based on aquatic gymnastic exercises aimed at muscular strengthening of the upper and lower extremities, as well as coordination, balance, agility, cycling and walking exercises submerged in water. The protocols developed to improve functional fitness in adults aged 50 to 80 years were based on general physical exercise prescription guidelines (frequency, duration, intensity and type of activity). The application of aquatic exercises based on gymnastic exercises can provoke positive responses on functional fitness if worked at least 2 to 5 times per week, 30 to 60min/day and at intensities of 50 to 95%. These systematized indicators can be used by professionals working with adults to create and promote aquatic programs to improve functional fitness.